Comparison between two selected Saccharomyces cerevisiae strains as fermentation starters in the production of traditional cachaça - Gomes,Fátima de Cássia Oliveira (2009)
Two Saccharomyces cerevisiae strains were tested as the starter yeasts in a traditional cachaça distillery. The strains used were S. cerevisiae UFMG-A829, isolated from a cachaça fermentation process, and S. cerevisiae K1-V1116, obtained from the wine industry. The permanence of each strain in the fermentation must was determined by RAPD (Random Amplified Polymorphic DNA)-PCR, with primer M13. Both yeast strains were prevalent in the vats for approximately 30 days. Indigenous non-Saccharomyces and indigenous S. cerevisiae strains were isolated in lower counts during the fermentation period. Indigenous S. cerevisiae strains were molecularly distinct when compared to the starter yeasts. The two yeasts appeared promising starter yeasts in the fermentation process to produce traditional cachaça.